Microbial diversity of the remote Trindade Island, Brazil: a systematic review - Yupanqui García,Glen Jasper; Badotti,Fernanda; Ferreira-Silva,Alice; da Cruz Ferraz Dutra,Joyce; Martins-Cunha,Kelmer; Gomes,Rosimeire Floripes; Costa-Rezende,Diogo; Mendes-Pereira,Thairine; Delgado Barrera,Carmen; Drechsler-Santos,Elisandro Ricardo; Góes-Neto,Aristóteles (PeerJ, 2025)
Trindade Island is a unique volcanic environment in the South Atlantic, characterized by acidic soils, rich organic matter and a high diversity of micro- and macroorganisms. Such diversity can represent a range of ecological niches and functions, potentially offering valuable ecosystem services. This systematic review aimed to synthesize the current knowledge of the island’s microbial communities, focusing on their ecological roles and biotechnological potential. Following the PRISMA guidelines, a comprehensive search of the scientific literature was conducted to identify studies that performed DNA sequencing of samples collected on Trindade Island, Brazil. The selected studies used approaches, such as shotgun metagenomics and marker gene sequencing, including samples from microcosm experiments and culture-dependent samples. A total of eight studies were selected, but only six provided detailed taxonomic information, from which more than 850 genera of Bacteria, Archaea, and Fungi were catalogued. Soil communities were dominated by Actinobacteriota, Acidobacteriota, and Ascomycota (Fungi) while marine and coral environments showed high diversity of Pseudomonadota and Cyanobacteria. Microcosm experiments revealed adaptive responses to hydrocarbon contamination, mainly for Alcanivorax and Mortierella (Fungi). Compared to other ecosystems, such as the oligotrophic Galapagos Islands and the sea-restricted Cuatro Cienegas Basin, Cyanobacteria were shown to be more adaptive.
Keywords: Trindade Island; Microbial composition; Metagenomics; Metabarcoding